2005
DOI: 10.1002/path.1726
|View full text |Cite
|
Sign up to set email alerts
|

SPLUNC1 (PLUNC) is expressed in glandular tissues of the respiratory tract and in lung tumours with a glandular phenotype

Abstract: Short PLUNC1 (SPLUNC1) is the founding member of a novel family of proteins (PLUNC) expressed in the upper respiratory tract that may function in host defence. It is one of the most highly expressed genes in the upper airways and the protein has been detected in sputum and nasal secretions. This study describes, for the first time, the precise cellular localization of SPLUNC1 in human tissues from the respiratory tract. Although SPLUNC1 is found in some epithelial cells of the upper airways and coats the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
90
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 23 publications
12
90
0
Order By: Relevance
“…The original PLUNC gene, which is now called SPLUNC1, comprises up to 10% of total protein in the airway surface liquid, and can readily be detected in both nasal lavage and tracheal secretions (14)(15)(16). SPLUNC1 is expressed in both submucosal glands, the superficial epithelia and in neutrophils, and in theory, is present in the correct regions of the lung to be a volume sensing molecule, because it can be secreted onto the mucosal surface of the superficial epithelial where ENaC is expressed (17,18). Thus, because SPLUNC1 bound to trypsin, we initiated studies to better characterize SPLUNC1 function and to determine whether it was a soluble regulator of ENaC.…”
mentioning
confidence: 99%
“…The original PLUNC gene, which is now called SPLUNC1, comprises up to 10% of total protein in the airway surface liquid, and can readily be detected in both nasal lavage and tracheal secretions (14)(15)(16). SPLUNC1 is expressed in both submucosal glands, the superficial epithelia and in neutrophils, and in theory, is present in the correct regions of the lung to be a volume sensing molecule, because it can be secreted onto the mucosal surface of the superficial epithelial where ENaC is expressed (17,18). Thus, because SPLUNC1 bound to trypsin, we initiated studies to better characterize SPLUNC1 function and to determine whether it was a soluble regulator of ENaC.…”
mentioning
confidence: 99%
“…14 Immunohistochemical analysis of PLUNC in lung cancer revealed that PLUNC is commonly expressed in adenocarcinoma, mucoepidermoid carcinoma, and bronchoalveolar carcinoma and is absent from small cell carcinoma and squamous cell carcinoma. 15 Although PLUNC is a major secreted protein product in the upper respiratory tract, 15 the biologic function of PLUNC is poorly understood.…”
mentioning
confidence: 99%
“…Other proteomic studies identified high expression of BPIFA1 in CRS nasal mucosa tissue and verified this observation by immunohistochemistry (16). Since BPIFA1 is well expressed in submucosal glands in the respiratory tract (21,22), its overexpression in CRS sinonasal secretions further supports submucosal gland hyperplasia in CRS sinus mucosa. DMBT1, also known as GP340, is a glycoprotein implicated in immune response (23), mucosal inflammation and epithelial regeneration (24).…”
Section: Discussionmentioning
confidence: 72%